ANALYSIS OF COLLABORATION BETWEEN GOVERNMENT, PRIVATE SECTOR, AND COMMUNITY IN THE IMPLEMENTATION OF TOURISM EVENTS IN LAMPUNG PROVINCE - Maharani Actaria; Malik Malik (International Journal of Multidisciplinary Reseach, 2026)
The research method used is descriptive qualitative research. This method is used to describe the analysis of collaboration between government, private sector, and community in marketing tourism events in Lampung Province. All data was obtained directly from informants in the field using interviews and document studies. The results of the study indicate that, in the Analysis of Collaboration Between Government, Private Sector, and Community in Marketing Tourism Events in Lampung Province, collaboration between the government, private sector, and community in implementing tourism events in Lampung Province has, in principle, been ongoing, but is not yet optimal. This collaboration still faces various structural and functional obstacles, particularly in unifying the vision between actors, increasing local capacity, and ensuring the economic and social sustainability of events. Differing interests, limited community capacity, and the short-term orientation of events mean that the impacts of tourism have not been felt evenly and sustainably by local communities.